2004
DOI: 10.1016/s0736-0266(03)00134-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical analysis of the femoral condyle in normal and osteoarthritic knees

Abstract: It is important to understand anatomical feature of the distal femoral condyle for treatment of osteoarthritic knees. Detailed measurement of the femoral condyle geometry, however, has not been available in osteoarthritic knees including valgus deformity. This study evaluated femoral condyle geometry in 30 normal knees, 30 osteoarthritic knees with varus deformity, and 30 osteoarthritic knees with valgus deformity using radiographs and magnetic resonance imaging (MRI). In radiographic analysis in the coronal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 21 publications
6
80
3
1
Order By: Relevance
“…17 Our findings are consistent with these studies, as we found our axis of rotation marked as per anterior referencing (A) to he always consistent with E; unlike axis of rotation marked as per posterior referencing (P),which showed a discrepancy in 30% cases, causing internal rotation. 10,[15][16][17] Our findings were consistent with Matsuda et al in the fact that 6 of our knees which showed excessive internal rotation, using posterior referencing had a valgoid deformity, however excessive internal rotation in the remaining 18 knees was due to hypertrophy of the medial condyle. 17 This could be attributable to the late presentation of hypertrophic osteoarthritis in Indian population.…”
Section: 215-17supporting
confidence: 92%
See 1 more Smart Citation
“…17 Our findings are consistent with these studies, as we found our axis of rotation marked as per anterior referencing (A) to he always consistent with E; unlike axis of rotation marked as per posterior referencing (P),which showed a discrepancy in 30% cases, causing internal rotation. 10,[15][16][17] Our findings were consistent with Matsuda et al in the fact that 6 of our knees which showed excessive internal rotation, using posterior referencing had a valgoid deformity, however excessive internal rotation in the remaining 18 knees was due to hypertrophy of the medial condyle. 17 This could be attributable to the late presentation of hypertrophic osteoarthritis in Indian population.…”
Section: 215-17supporting
confidence: 92%
“…10,[15][16][17] Our findings were consistent with Matsuda et al in the fact that 6 of our knees which showed excessive internal rotation, using posterior referencing had a valgoid deformity, however excessive internal rotation in the remaining 18 knees was due to hypertrophy of the medial condyle. 17 This could be attributable to the late presentation of hypertrophic osteoarthritis in Indian population.…”
Section: 215-17supporting
confidence: 91%
“…However, in varus knees, an excessive rotational angle may be applied because of cartilage surface destruction, resulting in the creation of a greater flexion gap and medial instability, patellar dislocations, and subluxation. In contrast, in the valgus knees, 38 of external rotation from the posterior condyles causes internal rotation of the femoral component relative to the TEA due to lateral condyle erosion [13]. Moreover, when PCA is used as the reference axis, it is difficult to insert the rotational guide needed to make complete contact with the posterior condyles, and the most posterior point of the medial and lateral femoral condyles is often not seen as a result of osteophytes, joint narrowing, and meniscus.…”
Section: Discussionmentioning
confidence: 96%
“…First, it was performed on arthritic knees and this could have an influence on the results attributable particularly to cartilage erosion, especially in the posterior condyles. Matsuda et al [16] performed a study to compare normal and osteoarthritic knees and found the latter knees differ from normal only in the valgus deformity population, whereas there was no major difference in patients with varus deformity. The increased external rotation observed in valgus knees is likely the consequence of lateral femoral condyle erosion or hypoplasia in valgus knees.…”
Section: Discussionmentioning
confidence: 99%